MiR-182 contributes to cell proliferation, invasion and tumor growth in colorectal cancer by targeting DAB2IP. (June 2019) - Li, Xiaoli; Zhang, Xudong; Zhang, Qiuge; Lin, Rui
Abstract: miR-182 was revealed to be upregulated in colorectal cancer (CRC) and contributed to CRC development. However, the detailed molecular mechanism of miR-182 in the progression of CRC remains largely elusive. Herein, miR-182 was upregulated in CRC serum samples, CRC tissues and cells. miR-182 expression was evidently reduced in postoperative serum samples, compared with preoperative serum samples, whereas miR-182 expression was re-elevated in serum samples from CRC patients who developed postoperative recurrence. Exogenous miR-182 promoted the proliferation, colony formation, increased ki67 level and facilitated the invasion capability of CRC cells by enhancing the expressions of MMP-2 and MMP-9, while inhibition of miR-182 showed the opposite effects. Additionally, miR-182 was demonstrated to target DAB2IP and suppress its expression in CRC cells. Downregulation of miR-182 inhibited CRC tumor growth in vivo by upregulating DAB2IP. Moreover, restoration of DAB2IP attenuated miR-182-mediated activation of the PI3K/Akt/mTOR and Wnt/β-catenin pathways in CRC cells. Taken together, our findings showed that miR-182 exerted its oncogenic role in CRC by targeting DAB2IP, which may be involved in activating the PI3K/Akt/mTOR and Wnt/β-catenin pathways, shedding a novel light on the molecular mechanism of CRC tumorigenesis.